'Bastard children': unacknowledged consulting companies in development cooperation. Issue 2 (April 2020) - White, Pamela
Abstract : Development consulting companies are pivotal actors in bilateral projects, yet they are largely invisible in policy documents, and little researched. Their business model is a combination of 'doing good' and profit. This article examines the history, business logics and working relationships of consulting companies in development cooperation, taking the case of Finland. It asks 'Why are consultancy companies needed in development cooperation?' Their relationship with donors appears to represent a principal–agent relationship, yet they often share the donor's ethos, and even exchange staff. The dramatic decrease in technical assistance budgets over recent years, along with increasing bureaucracy, has caused profits to diminish and many companies have disappeared, taking institutional memory with them. However, if the donors wish to assert some policy guidance and have contact with work on the ground in developing countries, there is a need for technical assistance via consulting companies.